On-body transmission performance of a novel dual-mode wearable microstrip antenna - Mendes, Carlos (2018)
The path loss established between several wearable antenas placed on a tissue-equivalent phantom is investigated through numerical simulations and measurements. The on-body performance of a previously proposed dual-mode wearable textile antenna, designed to operate in the 2.45 GHz industrial, scientific and medical band, is evaluated and compared with a wearable textile patch antenna. Simulation results of a _/4 resonant wire monopole are also presented to serve as a reference. Five different scenarios for the location of the transmitting and receiving antennas are analyzed: one with line of sight (LOS), two with non- LOS (NLOS), and the remaining two in the transition between LOS and NLOS. The transmission results are evaluated with the antenas mounted on the surface of a homogeneous phantom with 2/3 muscle properties mimicking the shape and physical macroscopic properties of a human torso. A general good agreement is obtained between numerical simulation and experimental results. It is shown that in the NLOS scenario, the proposed antenna has an equivalent path loss only about 3.4 dB higher than the monopole and about 10 dB lower than the patch.